The legal status of the partner during the establishment of the Commercial Solidarity Company - Jajan, AbdulRazzaq Omar; Al-Sulami, Muhammed Qabil (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to examine the legal provisions governing partners in joint stock companies in the event of the company’s establishment. The partner in a joint stock company is the person who contributes a share to the company, which may be in cash or in kind. The partner may contribute their share as an act, and a company cannot be established without the condition of consent, meaning that all partners must agree that the company is a contract that requires consent. Additionally, legal capacity is required for commercial purposes, and minors cannot be joint partners because they are not eligible to be merchants, The management of the partnership company is undertaken by its partners. All partners acquire merchant status upon joining the company, even if they were not merchants before, when the purpose of the company is to engage in commercial activities. The commercial status granted to partners upon joining a joint stock company is based on several considerations, including that the partner assumes full responsibility for the company’s activities and their fate is tied to it. In this research, we will discuss the personal and solidarity responsibility of partners in cooperative companies. It clarifies the partner’s responsibility for the debts of the company prior to joining and for the debts of the company after joining, in addition to revealing the responsibility that falls on the partner in case of loss. The most important consequence is that bankruptcy of the company entails by law, bankruptcy of all joint partners. As a merchant and responsible for company debts, partnership responsibility is both solidarity and absolute. Therefore, if the company stops paying its debts, this leads to joint partners also stopping payment of their debts. The responsibility of partners for cooperative company debts is both personal and solidarity-based, and creditors have the right to claim their rights from partners collectively or individually. However, it is permissible in a founding contract to agree on different percentages according to legal regulations. If a partner’s share is limited to work only and they are not assigned a share in profit or loss in founding contract, their share will be based on their percentage at founding evaluation. If multiple partners work without evaluating each other’s shares, these shares are considered equal unless proven otherwise.